Traditional circumcision during manhood initiation rituals in the Eastern Cape, South Africa: a pre-post intervention evaluation - Nqeketo Ayanda; Peltzer Karl; Petros George; Kanta Xola (BMC, 2008)
Abstract Background Circumcisions undertaken in non-clinical settings can have significant risks of serious adverse events, including death. The aim of this study was to test an intervention for safe traditional circumcision in the context of initiation into manhood among the Xhosa, Eastern Cape, South Africa. Methods Traditional surgeons and nurses registered with the health department were trained over five days on ten modules including safe circumcision, infection control, anatomy, post-operative care, detection and early management of complications and sexual health education. Initiates from initiation schools of the trained surgeons and nurses were examined and interviewed on 2nd, 4th, 7th and 14th day after circumcision. Results From 192 initiates physically examined at the 14th day after circumcision by a trained clinical nurse high rates of complications were found: 40 (20.8%) had mild delayed wound healing, 31 (16.2%) had a mild wound infection, 22 (10.5%) mild pain and 20 (10.4%) had insufficient skin removed. Most traditional surgeons and nurses wore gloves during operation and care but did not use the recommended circumcision instrument. Only 12% of the initiates were circumcised before their sexual debut and they reported a great deal of sexual risk behaviour. Conclusion Findings show weak support for scaling up traditional male circumcision.